Pedagogia do re-encantamento: uma intervenção diferencial na formação docente - Camolez, João Carlos (2007)
This dissertation is a study about the impacts of differential formation to teachers, entitled reinchantment pedagogy. That intervention was realized with teachers of the public school from São Paulo suburbs. The research inquired the contribution provided from that intervention, pointing out the changes occurred and the relations from that with the overcome of teacher unrest and with pedagogical practice of the teachers involved in formation meet.